Identification of four immune subtypes in locally advanced rectal cancer treated with neoadjuvant chemotherapy for predicting the efficacy of subsequent immune checkpoint blockade - He, Le; Jin, Min; Jian, Dan; Yang, Bo; Dai, Nan; Feng, Yan; Xiao, He; Wang, Dong (Frontiers in Immunology, 2022)
Introduction: Neoadjuvant chemoradiotherapy (nCRT) was the foundation treatment for locally advanced rectal cancer (LARC). The nCRT can improve the efficacy of immunotherapy on account of its in-situ vaccine effect. Objective: The aim is to identify stable and reliable transcriptome signatures to predict the efficacy of immune checkpoint blockade (ICB) in patients with LARC. Methods: Immunophenotyping was established by using xCell immune cell infiltration abundance and consistent clustering in GSE39582 and verified in several data sets. The effects of immunophenotyping, follicular regulatory T cells, tumor associated fibroblasts (CAF) and tertiary lymphoid structures (TLS) signatures on the efficacy of ICB were analyzed by using IMvigor210, GSE91061 and an independent Daping Hospital (DPH) cohort. Results: There are four stable and repeatable immune subtypes in rectal cancer, among which C1 is low immune infiltration type, C2 is high interstitial infiltration type, C3 is high immune infiltration type and C4 is ion channel type. C2 is mainly characterized by high infiltration CAF, C3 is characterized by high infiltration of cytotoxic T lymphocytes, high expression of PD-L1 and TLS. In rectal cancer patients receiving nCRT, immunophenotyping was not significantly associated with pathological remission rate, but immunophenotyping was an independent prognostic factor of RFS. In IMvigor210 patients treatment with atezolizumab, the pathological remission rates of C1, C2, C3 and C4 were 23.86%, 10.94%, 33.33% and 23.08% respectively (χ2 = 8.981, P = 0.029), which were 11.76%, 50.00%, 42.86% and 0.0% respectively in the GSE91061 patients treatment with nivolumab (Fisher's exact probability, P = 0.018). Both follicular regulatory T cells and CAF showed a further impact on the ICB therapeutic efficacy of C2 and C3 subtype. In addition, both GSE91404 and DPH cohorts showed that nCRT treatment induced a significant increase in the expression of TNFRSF9 and abundance of macrophages in C3 subtype. Conclusion: Our data suggest that there are four immune types of rectal cancer, which are related to the prognosis of patients. Among them, C3 and some C2 subtypes represents the patients who may benefit from ICB after nCRT treatment.